UV photodegradation of methylene blue using microstructural carbon materials derived from citrullus colocynthis - Bhatti, Muhammad Ali; Dawi, Elmuez; Tahira, Aneela; Hulio, Ahmed Ali; Halepoto, Imran Ali; Chang, Sajjad Ali; Solangi, Abdul Ghaffar; Nafady, Ayman; Tonezzer, Matteo; Haj Ismail, Abd Al Karim; Ibupoto, Zafar Hussain (Frontiers in Materials, 2024)
A low temperature aqueous growth followed by mild pyrolysis was used in this study to synthesize high-quality carbonized materials from the deserted plant Citrullus Colocynthis. It was found that the carbon material prepared for this study contained an abundance of functional groups and surface active sites. A few microns were evidently the size of the carbon material. This study investigated a variety of photocatalytic performance evaluation parameters, including initial dye concentration of methylene blue, pH effect on dye solution, scavenger stability, and recycle stability via irradiating UV light. Methylene blue degradation was found to be significantly affected by pH and concentration of the dye solution. It has been found that pH 5 is the most effective pH for the removal of dyes. As a result of the study, we found that MB decays according to pseudo first order kinetics and is estimated to remove dye at an almost 100% rate.